ChemInform Abstract: Divergent Synthesis of 2‐Aminofurans via Palladium‐Catalyzed Acetoxylative, Alkoxylative, and Hydroxylative Cycloisomerization of Homoallenyl Amides. Issue 49 (December 2015) - Cheng, Cungui; Liu, Shuiyou; Zhu, Gangguo
Abstract: using hypervalent iodine organic compounds as oxidant